Agências reguladoras: uma promessa não realizada contra o risco da captura. - Luz Neto, Luiz Guedes da (2016)
The dissertation has as its theme the capture of the regulator, in particular the Regulatory Agencies implemented in the legal system from the American model with the administrative reform carried out with more emphasis in the government of Fernando Henrique Cardoso. In this reform, the regulatory agencies have been placed as a modern model and legal certainty generator, considering that their leaders, because they are technical professionals in the regulated area, would be more protected from outside influence, and thus harder to regulatory capture. Notwithstanding the model "modern" presented the facts demonstrated the capture of leaders of regulatory agencies, not fulfilling these ones promised in the administrative reform of the 1990s in Brazil. They will be analyzed in the first chapter, the historical and economic assumptions of regulatory agencies; in the second chapter, it analyzes will be the regulatory agencies, and in the latter the phenomenon of regulatory capture of the agencies. From the combination of the theoretical framework of the Theory of Economic Regulation (economic theory of capture), George J. Stigler, and the notion of State from Leon Duguit, state-fact theory, the conclusion about the capture of the dynamics will be made of specific regulatory entities, called Independent Regulatory Agencies.